Interplanetary Scintillation with the Murchison Widefield Array V: An all-sky survey of compact sources using a modern low-frequency radio telescope. (28th January 2019) - Morgan, J. S.; Macquart, J.-P.; Chhetri, R.; Ekers, R. D.; Tingay, S. J.; Sadler, E. M.
Abstract: We describe the parameters of a low-frequency all-sky survey of compact radio sources using Interplanetary Scintillation, undertaken with the Murchison Widefield Array. While this survey gives important complementary information to low-resolution survey, providing information on the sub-arsecond structure of every source, a survey of this kind has not been attempted in the era of low-frequency imaging arrays such as the Murchison Widefield Array and LOw Frequency Array. Here we set out the capabilities of such a survey, describing the limitations imposed by the heliocentric observing geometry and by the instrument itself. We demonstrate the potential for Interplanetary Scintillation measurements at any point on the celestial sphere and we show that at 160 MHz, reasonable results can be obtained within 30° of the ecliptic (2 π str: half the sky). We also suggest some observational strategies and describe the first such survey, the Murchison Widefield Array Phase I Interplanetary Scintillation survey. Finally we analyse the potential of the recently upgraded Murchison Widefield Array and discuss the potential of the Square Kilometre Array-low to use Interplanetary Scintillation to probe sub-mJy flux density levels at sub-arcsecond angular resolution.